The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1590/1981-81222014000300012
|View full text |Cite
|
Sign up to set email alerts
|

Morfologia craniana dos remanescentes ósseos humanos da Lapa do Santo, Lagoa Santa, Minas Gerais, Brasil: implicações para o povoamento das Américas

Abstract: Abstract:The karstic region of Lagoa Santa has been highly important for the discussion about the tempo and mode of the initial human dispersal into the Americas. Lapa do Santo rockshelter, excavated during the past decade, represents to date one of the largest collections of early Holocene human remains recovered from the region. Here we analyze the morphological affinities of Lapa do Santo individuals with other early series from Lagoa Santa and Colombia, contextualizing them within the modern human cranial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
(47 reference statements)
0
3
0
1
Order By: Relevance
“…Archaeological research in the Lagoa Santa region identified the evidence of human groups in shelters dating back to Late Pleistocene or early Holocene (Araújo et al., ; da Gloria et al., ; Laming‐Emperaire, Prous, Vilhena de Morais, & Beltrão, ; Neves et al., ; Prous, 1992/1993; Strauss et al., ). The systematic study of more than 300 human skeletons by Neves, Prous, González‐José, Kipnis, and Powell () revealed an ancient immigration by Australo‐Melanesian people, leading to the disputed proposal of “two main biological components” for the human occupation of South America (Neves et al., , ; Neves & Pucciarelli, ).…”
Section: Regional Archaeological Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Archaeological research in the Lagoa Santa region identified the evidence of human groups in shelters dating back to Late Pleistocene or early Holocene (Araújo et al., ; da Gloria et al., ; Laming‐Emperaire, Prous, Vilhena de Morais, & Beltrão, ; Neves et al., ; Prous, 1992/1993; Strauss et al., ). The systematic study of more than 300 human skeletons by Neves, Prous, González‐José, Kipnis, and Powell () revealed an ancient immigration by Australo‐Melanesian people, leading to the disputed proposal of “two main biological components” for the human occupation of South America (Neves et al., , ; Neves & Pucciarelli, ).…”
Section: Regional Archaeological Settingmentioning
confidence: 99%
“…(Gif ‐ 5088), people used the shelter for burial (Prous, 1992/1993). The skeletons found displayed physical characteristics of a population known as “Lagoa Santa people,” with distinctly archaic cranial features associated with Australo‐Melanesian and African affinities (Neves, & Hubbe, ; Neves, Hubbe, Strauss, & Bernardo, ; Neves, Powell, Prous, Ozolins, & Blum, ).…”
Section: Introductionmentioning
confidence: 99%
“…The work by Neves and Pucciarelli sparked decades of research, with dozens of articles published by different research groups dedicated to elucidating the origins of the morphological affinities observed among the Lagoa Santa collections . Today, the Lagoa Santa skeletal collection is unique in terms of sample size for early Americans, counting with at least 88 measurable crania found in an area of about 400 km 2 …”
Section: Who Were the First Populations That Occupied Lagoa Santa?mentioning
confidence: 97%
“…Inúmeras datações radiocarbônicas foram feitas a partir de carvões e ossos humanos, resultando em datas entre 10.490 ± 50 aP e 790 ± 40 aP (Tabela Suplementar 3; Araujo et al 2012; Strauss et al 2016). Muito foi produzido sobre o sítio, incluindo análises sobre os processos de formação (Villagran et al 2017), estudos sobre a indústria lítica (Araujo et al 2017; Bueno 2012; Moreno de Sousa e Araujo 2018; Pugliese 2007), indústria óssea (Santos 2011), padrões de sepultamento (Strauss et al 2016), biodistância (Neves et al 2014; Nunes 2010; Posth et al 2018) e remanescentes arqueofaunísticos (Bissaro 2008; Mingatos 2017; Mingatos e Okumura 2016; Perez 2009). A partir dos estudos zooarqueológicos, foi possível observar uma permanência dos hábitos alimentares ao longo do Holoceno (Araujo et al 2017) e, principalmente, o consumo majoritário de cervídeos, especialmente os do gênero Mazama , por essa população (Mingatos 2017; Perez 2009).…”
Section: Materiais E Métodosunclassified